Low dose mifepristone in the treatment of uterine leiomyoma - Hangarga, U. S.; D., Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To determine and evaluate the effectiveness of low dose of mifepristone in the management of symptomatic leiomyoma. Methods: It is a randomized prospective observational before after treatment study of 50mg mifepristone once weekly for 24weeks (6 Months). The study was conducted at Navodaya Medical College Hospital and Research Centre, Raichur. The study period was Jan-June 2016; the total of 30 patients was enrolled in the study. Sample size was calculated to study changes in various parameters after 6months of treatment with mifepristone 50mg weekly. Basic investigations were performed, which includes Hb%, LFT, RFT, Complete Hemogram, USG examinations including Doppler study and menstrual blood loss was calculated through pictoral blood assessment chart. Improvement of the patient was assessed at 1, 3 and 6 months. Results: The majority of our study group patients belong to between 40-45 years and 66% of patients were para-2. The most important dominant symptom was menorrhagia, out of 30 patients, 27 had excessive blood loss during periods (90%). All 30 cases were subjected to endometrial biopsy before starting of treatment; there was a change in the endometrial pattern after treatment. The marked changes in the endometrium were simple endometrial hyperplasia and decrease in the normal endometrial pattern after treatment. In the present study after starting the treatment there was reduction in menstrual blood loss observed in 90% of patients and 75% of patients’ attained amenorrhea at the end of treatment, improvement in haemoglobin parameter in the study group. The size of fibroids was also decreased. Conclusions: Low dose mifepristone treatment for leiomyoma is more efficacious and useful to the patient. Drug helped in reliving the symptoms of the patient to a greater extent.